The Computational fluid dynamics Performance Analysis of Horizontal Axis Wind Turbine - Naji Abdullah Mezaal; Osintsev K. V.; Alyukov S.V. (Institute of Advanced Engineering and Science, 2019)
Computational fluid dynamics (CFD) simulations were performed in the present study using ANSYS Fluent 18.0, a commercially available CFD package, to characterize the behaviour of the new HAWT. Static three-dimensional CFD simulations were conducted. The static torque characteristics of the turbine and the simplicity of design highlight its suitability for the GE 1.5xle turbine. The major factor for generating the power through the HAWT is the velocity of air and the position of the blade angle in the HAWT blade assembly. The study presents the effect of The blade is 43.2 meters long and starts with a cylindrical shape at the root and then transitions to the airfoils S818, S825 and S826 for the root, body and tip, respectively. This blade also has pitch to vary as a function of radius, giving it a twist and the pitch angle at the blade tip is 4 degrees. This blade was created to be similar in size to a GE 1.5xle turbine by Cornell University [1]. In addition, note that to represent the blade being connected to a hub, the blade root is offset from the axis of rotation by 1 meter. The hub is not included in our model. The experimental analysis of GE 1.5xle turbine, so that possible the result of CFD analysis can be compared with theoretical calculations. CFD workbench of ANSYS is used to carry out the virtue simulation and testing. The software generated test results are validated through the experimental readings. Through this obtainable result will be in the means of maximum constant power generation from HAWT.